Fluorescence of solvent-extractable organics in sub-micrometer forest aerosols in Hokkaido, Japan. (15th June 2023) - Afsana, Sonia; Zhou, Ruichen; Miyazaki, Yuzo; Tachibana, Eri; Deshmukh, Dhananjay Kumar; Kawamura, Kimitaka; Mochida, Michihiro
Abstract: Excitation–emission matrix (EEM) fluorescence spectroscopy is an analytical method for obtaining the properties, components, and sources of chromophores of atmospheric organic aerosols (OA). Most studies have been limited to water-soluble OA; the chemical structures of OA associated with chromophores and the sources of chromophores are still not well understood. In this study, the fluorescence properties of solvent-extractable organic components, fractionated based on their polarity in sub-micrometer forest aerosols in Hokkaido, Japan, were characterized on the basis of their EEMs in combination with chemical structural characterization from offline aerosol mass spectrometry. The fluorescence volume normalized by the mass concentration (NFV) and the fluorescence volume (FV) corresponding to the atmospheric abundance for water-insoluble organic matter (WISOM) were higher than those of other OA fractions and highest in the winter. Correlation analyses between the NFVs and the relative intensities of ion groups from the mass spectra from a high-resolution aerosol mass spectrometer suggest that organic compounds containing O and N contributed to the fluorescence of the OA fractions. Although the fluorescence indices used to characterize aquatic dissolved organic matter exhibited comparable values for water-soluble organic matter (WSOM) in this study and in previous studies, they are not applicable in explaining the types or sources of other OA fractions. A parallel factor (PARAFAC) analysis for EEM profiles identified five components. Four components had fluorescence characteristics similar to those associated with humic-like substances (HULIS), and one had fluorescence characteristics associated with protein-like compounds (PLOM). The chromophores commonly associated with HULIS with oxygenated structures contributed significantly to respective OA fractions; this implies that for fluorescence measurements, such as the detection of primary biological aerosol particles (PBAP), contributions from oxygenated organics should be considered in the forest region. Highlights: The EEM spectra of fractionated organic aerosol components were characterized for sub-micrometer aerosols in a forest. Water-insoluble organic matter had a higher fluorescence intensity than other organic aerosol fractions. Organic aerosol fractions had high fluorescence intensity in winter. Five independent components were identified from PARAFAC analysis. HULIS-like components were the main fluorophores.